Studi Komparatif Perlindungan terhadap Anak sebagai Saksi Kejahatan Seksual - Fitria Rahma Azahra; Nandang Sambas (Jurnal Riset Ilmu Hukum, 2024)
Abstract. Human protection is an important aspect in the continuity of human life that cannot be taken by force or separated from human existence, each individual must be protected from criminal acts that result in the deprivation of the right to freedom of life of each individual, one of which is sexual crime, in fact in various countries, one of which is Indonesia and Germany, the majority of victims of sexual crimes are minors. The problems in this study are (1) whether the implementation of child witness protection in Indonesia and Germany is in accordance with the laws in each country, and (2) whether the handling by the institution has provided a sense of security for child witnesses of sexual crimes. By using comparative juridical, the results of this research are: that the implementation of regulations on the protection of child victims of sexual crimes in both countries is in accordance with the regulations on the protection of witnesses and victims. The handling carried out by the institution in protecting witnesses and victims has provided a sense of security for child witnesses of sexual crimes. Abstrak. Perlindungan manusia adalah aspek penting didalam keberlangsungan kehidupan manusia yang tidak dapat diambil paksa maupun di pisahkan keberadaan nya dari diri manusia, setiap individu harus terlindung dari tindak pidana kejahatan yang mengakibatkan terampasnya hak kebebasan hidup setiap individu, salah satunya tindak pidana kejahatan seksual, faktanya di berbagai negara salah satunya Indonesia dan Jerman mayoritas korban tindak pidana kejahatan seksual adalah anak dibawah umur. Permasalahan di dalam penelitian ini adalah (1) Apakah pelaksanaan perlindungan saksi anak di Indonesia dengan negara Jerman telah sesuai dengan undang-undang di masing-masing negara, dan (2) Apakah penanganan yang dilakukan lembaga telah memberikan rasa aman bagi saksi anak kejahatan seksual?. Dengan menggunakan yuridis komparatif, hasil dari penelitian ini adalah : bahwa pelaksanaan peraturan perlindungan saksi korban anak kejahatan seksual di kedua negara telah sesuai dengan peraturan perlindungan saksi dan korban. Penanganan yang dilaksanakan lembaga dalam melindungi saksi dan korban telah memberikan rasa aman bagi saksi anak tindak pidana kejahatan seksual